A systematic literature review of leptospirosis outbreaks worldwide, 1970-2012 - Claudia Munoz-Zanzi; Emily Groene; Bozena M. Morawski; Kimberly Bonner; Federico Costa; Eric Bertherat; Maria Cristina Schneider (Pan American Health Organization, 2020)
Objective. This review describes the geographic and temporal distribution of, detection methods for, and other epidemiological features of published leptospirosis outbreaks, with the aim of informing efforts to standardize outbreak-reporting practices. Methods. We conducted a systematic review of leptospirosis outbreaks reported in the scientific literature and ProMED during 1970-2012. Predefined criteria were used to identify and classify outbreaks and a standard form was used to extract information. Results. During 1970-2012, we identified 318 outbreaks (average: 7 outbreaks/year; range: 1-19). Most outbreaks were reported in the Latin America and the Caribbean region (36%), followed by Southern Asia (13%), and North America (11%). Most outbreaks were located in tropical and subtropical ecoregions (55%). Quality classification showed that there was clear description of laboratory-confirmed cases in 40% of outbreaks. Among those, the average outbreak size was 82 cases overall (range: 2-2 259) but reached 253 cases in tropical/subtropical ecoregions. Common risk factors included outdoor work activities (25%), exposure to floodwaters (23%), and recreational exposure to water (22%). Epidemiologic investigation was conducted in 80% of outbreaks, mainly as case interviews. Case fatality was 5% overall (range: 0%-60%). Conclusions. Outbreak reporting increased over the study period with outbreaks covering tropical and non-tropical regions. Outbreaks varied by size, setting, and risk factors; however, data reviewed often had limited information regarding diagnosis and epidemiology. Guidelines are recommended to develop standardized procedures for diagnostic and epidemiological investigations during an outbreak and for reporting.